2021
DOI: 10.20945/2359-3997000000400
|View full text |Cite
|
Sign up to set email alerts
|

Long-term obesity is associated with depression and neuroinflammation

Abstract: Objective: Obesity is characterized by a state of chronic, low-intensity systemic inflammation frequently associated with insulin resistance and dyslipidemia. Materials and methods: Given that chronic inflammation has been implicated in the pathogenesis of mood disorders, we investigated if chronic obesity that was initiated early in life – lasting through adulthood – could be more harmful to memory impairment and mood fluctuations such as depression. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Studies using diet-induced obesity models demonstrated a significant increase in inflammatory markers in the frontal cortex, such as tumour necrosis factor α (TNF-α) and interleukin-1 β (IL-1β), 72 and also demonstrated that HFD-induced obesity could cause a harmful influence on brain cortex bioenergetics. 73 Obese humans with high BMI (in particular, over 40) and without neurological diseases have reduced mRNA expression of the anti-inflammatory cytokine interleukin 10 (IL-10) and increased mRNA expression of the enzyme associated with cytotoxicity and apoptosis inducible nitric oxide synthase in the frontal cortex. 74 These alterations, especially associated with the dysregulation of pro- or anti-inflammatory cytokines, may indicate an intensified neuroinflammatory response in this brain region.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using diet-induced obesity models demonstrated a significant increase in inflammatory markers in the frontal cortex, such as tumour necrosis factor α (TNF-α) and interleukin-1 β (IL-1β), 72 and also demonstrated that HFD-induced obesity could cause a harmful influence on brain cortex bioenergetics. 73 Obese humans with high BMI (in particular, over 40) and without neurological diseases have reduced mRNA expression of the anti-inflammatory cytokine interleukin 10 (IL-10) and increased mRNA expression of the enzyme associated with cytotoxicity and apoptosis inducible nitric oxide synthase in the frontal cortex. 74 These alterations, especially associated with the dysregulation of pro- or anti-inflammatory cytokines, may indicate an intensified neuroinflammatory response in this brain region.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the protective effect of MED on depressive symptoms was noted to gradually decrease as BMI increased. The prevalence of depression is known to be increased in the setting of obesity, a condition that promotes inflammation as well as resistance to insulin and leptin (43,44). Thus, a combination of MED adherence and proper weight control is guaranteed to improve the effectiveness of MED adherence in regard to alleviating depression.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral cortex, also called gray matter, is the brain’s outermost layer, which plays a key role in many high-level functions, such as reasoning, emotion, problem solving, memory, language, and consciousness. Some studies have also demonstrated that HFD-induced obesity activates neuroinflammation mechanisms with harmful effects on the cerebral cortex [ 98 , 99 , 100 ].…”
Section: Obesity Induces Cognitive Declinementioning
confidence: 99%